Enhancing data collection for palaeoenvironmental approaches in anthracology: X-ray microCT and ecological anatomy - Calo, Cristina Marilin; Marconetto, Bernarda (Frontiers in Environmental Archaeology, 2025)
X-ray microtomography has emerged as a valuable technique in archaeology for over a decade, aiding in the recording, preservation, and analysis of artifacts. While its application to archaeobotanical remains is well-documented, its use to study archaeological wood charcoal remains limited to preliminary research. This work explores microtomography suitability for anthracological studies based on a paleoenvironmental perspective. Ten Amazonian wood charcoal samples were studied using experimental charring, X-ray microCT and image data processing and analysis. 2D and 3D measures of anatomical attributes sensitive to environmental conditions, integrated as vulnerability index and mineral bodies abundance, were performed and compared. Results indicate that 3D imaging yields comparable insights to 2D analysis while being more efficient. The study highlights the benefits of volumetric data in vulnerability index calculations and crystal quantification, providing greater accuracy than traditional 2D methods. While further validation is needed, microtomography shows promise in enhancing the speed and reliability of anthracological studies.